KEABSAHAN ALAT BUKTI DALAM ELECTRONIC TRAFFIC LAW ENFORCEMENT MENURUT HUKUM INDONESIA - Galuh Kusuma Wardani; Ismawati Septiningsih (Sebelas Maret University, 2025)
This study aims to determine the strength of evidence used in Electronic Traffic Law Enforcement (ETLE) according to Undang-Undang No. 8 Tahun 1981or KUHAP and according to Undang-Undang No. 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan.This research is a normative or doctrinal legal research with a case approach. The type of data used is secondary data. The technique used in collecting legal materials in this research is literature study or document study. This research uses a qualitative descriptive method analysis technique, which describes the problem with the theory obtained from the field and assembles it using a series of words or sentences on the data.Based on this research, it is found that according to KUHAP Electronic Traffic Law Enforcement (ETLE) has strong evidentiary power in traffic law enforcement in Indonesia. Electronic or electronically recorded evidence including, but not limited to, writings, sounds or images, maps, designs, photographs or the like are valid evidence, substantially supporting the Electronic Traffic Law Enforcement (ETLE) arrangements that have been regulated in Undang-Undang No. 22 Tahun 2009.